An intelligent embedded system for self-balancing personal transporter - Lu, Zhilong. (2011)
Robotic mobility technologies have become more and more popular over the past few years. The inverted pendulum model based robot is one of them. Two-wheeled inverted pendulum model based robot has a small footprint, and it can be used on various terrains. However, such robot is hard to be balanced. This project investigated the techniques involved in balancing such an unstable two-wheeled robotic platform. The objective is to design and implement a discrete digital control system that will provide the unstable robot ability of self-balance.